Possible Anxiolytic Effects of Cannabidiol (CBD) Administration on Feline Responses to a Fear Response Test - Nobuo Masataka (Animals)
In humans, cannabidiol (CBD), the primary non-addictive component of cannabis, is known to possess considerable therapeutic potential. The purpose of this study was to investigate the effects of CBD administration on reducing sound-induced fear in healthy domestic cats in a laboratory model of thunderstorm simulation. A total of 40 cats, each naïve to the current testing, were randomly assigned into either of two administration groups (CBD and placebo). Each group was then exposed to the thunderstorm test twice; once at the beginning of the administration (the administration of CBD at 4.0 mg/kg/day over a 2-week-period or the administration of the same amount of sunflower oil as a placebo) and once after the end of the administration. When undesirable urination was observed, occurrences of this behaviour were found to decrease significantly when CBD was administered. However, no such changes were recorded when the placebo was administered. These results indicate that CBD could be an effective option for the treatment of noise-induced fear.